Accreditation Preparation on Stress Levels and Performance of Medical Personnel - Hayatunufus, Hayatunufus; Idealistiana, Lia; Mariani, Mariani (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT The Ministry of Health of the Republic of Indonesia establishes an independent licensing body called hospital accreditation after verifying that the hospital meets the required hospital service standards. Nurses in hospitals have many duties and responsibilities determined by the hospital itself, so their work can pose a lot of pressure and responsibility. The results of initial research on nine nurses at RSIA Mutiara Bunda Cilegon showed that they experienced stress due to waiting for accreditation, which had an impact on their performance as nurses. This type of research is qualitative research. The research design used is the case control study method. Based on the results of statistical tests, no significant influence between accreditation preparation on stress levels and performance of medical personnel was analyzed. There is no influence between accreditation preparation and nurses' stress level. RSIA Mutiara Bunda Cilegon is expected to provide greater support to medical personnel during accreditation preparation, such as training, counseling, or welfare programs to reduce the level of stress experienced. Keywords: Accreditation Preparation, Stress Level, Nurse Performance